2020
DOI: 10.3847/1538-4357/ab6664
|View full text |Cite
|
Sign up to set email alerts
|

Penumbral Brightening Events Observed in AR NOAA 12546

Abstract: Penumbral transient brightening events have been attributed to magnetic reconnection episodes occurring in the low corona. We investigated the trigger mechanism of these events in active region NOAA 12546 by using multi-wavelength observations obtained with the Interferometric Bidimensional Spectrometer (IBIS), by the Solar Dynamics Observatory (SDO), the Interface Region Imaging Spectrograph (IRIS), and the Hinode satellites. We focused on the evolution of an area of the penumbra adjacent to two small-scale e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…IBIS full Stokes spectropolarimetric scans were used to identify possible signatures of magnetic field oscillations in circular polarization (CP) measurements in the umbra. A full account of the observations and data reduction techniques is provided in Stangalini et al (2018), Murabito et al (2020), Houston et al (2020), andStangalini et al (2021). Here, we precis the aspects that are relevant to this analysis.…”
Section: Ibis Observations and Methodsmentioning
confidence: 99%
“…IBIS full Stokes spectropolarimetric scans were used to identify possible signatures of magnetic field oscillations in circular polarization (CP) measurements in the umbra. A full account of the observations and data reduction techniques is provided in Stangalini et al (2018), Murabito et al (2020), Houston et al (2020), andStangalini et al (2021). Here, we precis the aspects that are relevant to this analysis.…”
Section: Ibis Observations and Methodsmentioning
confidence: 99%
“…In addition to radiometric calibration, polarimetric demodulation and cross-talk minimization between the Stokes parameters was included in the calibration process. This dataset was also studied in Stangalini et al [60], Murabito et al [61], Houston et al [62], Murabito et al [63] In order to ensure the reliability of the results, here we restrict our attention to the intensity and CP fluctuations only. This choice is also motivated by the fact that since the Ca II 854.2 nm spectral line often goes into emission, the estimation of the Doppler velocity may lead to inconsistencies [64].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to radiometric calibration, polarimetric demodulation and cross-talk minimization between the Stokes parameters was included in the calibration process. This dataset was also studied in Stangalini et al [60], Murabito et al [61], Houston et al [62], Murabito et al [63]…”
Section: Methodsmentioning
confidence: 99%
“…The dataset used in this work was acquired with the Interferometric BIdimensional Spectrometer (IBIS; Cavallini 2006) instrument at the Dunn Solar Telescope (DST) on 2016 May 20 under excellent seeing conditions for more than two hours, between 13:40-15:30 UT. This dataset has been the main focus of other studies (see, e.g., Stangalini et al 2018Stangalini et al , 2021Murabito et al 2019Murabito et al , 2020Houston et al 2020;Baker et al 2021), due to the quality of the data and the large-scale nature of the observed sunspot, which was the leading spot of AR 12546.…”
Section: Observational Datamentioning
confidence: 99%